κ-Opioid receptor stimulation reduces palmitate-induced apoptosis via Akt/eNOS signaling pathway - Yan Cui (Lipids in Health and Disease, 2019)
Abstract Background This study was designed to test the hypothesis that κ-opioid receptor (κ-OR) stimulation reduces palmitate-induced HUVECs apoptosis and to investigate its mechanisms. Methods HUVECs were subjected to sodium palmitate, apoptosis and cell viability were determined, HUVECs were treated with specific inhibitors to PI3K, Akt, eNOS and siRNAs targeting κ-OR and Akt. Groups were divided as follows: the control group, the sodium palmitate group, the sodium palmitate+U50,488H (a selective κ-OR agonist) group and the sodium palmitate+U50,488H + nor-BNI (a selective κ-OR antagonist) group. Results Treatment with sodium palmitate significantly reduced cell viability and increased apoptosis rate which were significantly alleviated by pretreatment with U50,488H, the effect of U50,488H was abolished by nor-BNI. Phosphorylation of Akt and eNOS, as well as NO production were attenuated and accompanied by an increased expression of caspase 3 when HUVECs were subjected to sodium palmitate, and all these changes were restored by pretreatment with U50,488H, the effects of U50,488H were abolished by nor-BNI, and specific inhibitors to PI3K, Akt, eNOS, respectively. SiRNAs targeting κ-OR or Akt abolished the effects of U50,488H on phosphorylation of Akt and eNOS as well as the expressions of caspase 3, Bax and Bcl-2. SiRNAs targeting Akt elicited no effect on the expression of κ-OR. Conclusion This study provides the evidence for the first time that κ-OR stimulation possesses anti-palmitate-induced apoptosis effect, which is mediated by PI3K/Akt/eNOS signaling pathway.